Prevalensi HIV dan HBV pada Kalangan Remaja - Patricia Gita Naully; Sitti Romlah (Jurnal Kesehatan, 2018)
Human Immunodeficiency Virus (HIV) is a virus that infects a human immune system. HIV route of transmission is similar to Hepatitis B Virus (HBV), which is a virus that causes cirrhosis and liver cancer. Infection of HIV and HBV still remain a health problem in Indonesia. In Cimahi City, the number of HIV case is increasing, including in teenagers. Therefore, this study aims to determine HIV and HBV prevalence among teenager aged 15-19 years old who live in sub-district South Cimahi. The sample used is from adolescents aged 15-19 years who live in District Cimahi South. Venipuncture is done only on respondents who have filled informed consent and questionnaire. Laboratory testing conducted consisted of anti-HIV and HBsAg testing using immunochromatography. Data obtained from laboratory testing is analyzed using a logistic regression method. Of 100 adolescence, one person is found infected with HIV and two are infected with HBV. Based on statistical data, age; education; and frequent changes in sexual partners, significantly influence the HIV prevalence (p <0.05). In HBV, factors that significantly influence prevalence are: age, education, piercing, and vaccination (p <0.05). From all the results it can be concluded that HIV and HBV case among adolescents aged 15-19 years found in sub-district of South Cimahi has the prevalence of 1% for HIV and 2% for HBV.